URGENSI PEMBENTUKAN POLISI KHUSUS PENGADILAN SEBAGAI UPAYA PEMENUHAN HAK JAMINAN KESELAMATAN HAKIM DI INDONESIA - Aditya Permana Putra (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
Special police force is not something new in Indonesia. At least there are four special police force in Indonesia namely Prison Guard, Railway Police, Civil Service Police, and Forestry Special Police. Those police force are separated from, but hand in hand with Indonesian Police Force in securing civil society in Indonesia. In regards with the security of judges in Indonesia, this paper tries to argue that they need special police force to guard and secure them. In this paper, it is concluded that it is required to change the Law regarding Judicial Power especially in the part concerning judge’s safety and security. If it is not probable, then creating a special police force in court is a must.